2016
DOI: 10.1002/ecy.1595
|View full text |Cite
|
Sign up to set email alerts
|

Resource stoichiometry and the biogeochemical consequences of nitrogen deposition in a mixed deciduous forest

Abstract: Ecosystems often show differential sensitivity to chronic nitrogen (N) deposition; hence, a critical challenge is to improve our understanding of how and why site-specific factors mediate biogeochemical responses to N enrichment. We examined the extent to which N impacts on soil carbon (C) and N dynamics depend on microbial resource stoichiometry. We added N to forest plots dominated by ectomycorrhizal (ECM) trees, which have litter and soil pools rich in organic N and relatively wide C:N ratios, and adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 69 publications
(109 reference statements)
7
43
1
Order By: Relevance
“…14 for AM stands and 28 for ECM stands. This relationship was consistent with Midgley and Phillips (), who observed a two‐fold difference in the ratio of C mineralisation to N mineralisation between AM and ECM plots. If the majority of additional plant growth went to woody tissue with a typical C : N ratio of 300 or more, priming effects would likely drive a net increase in total ecosystem C storage, although tree mortality or depletion of soil N over time could eventually limit this increase.…”
Section: Discussionsupporting
confidence: 91%
“…14 for AM stands and 28 for ECM stands. This relationship was consistent with Midgley and Phillips (), who observed a two‐fold difference in the ratio of C mineralisation to N mineralisation between AM and ECM plots. If the majority of additional plant growth went to woody tissue with a typical C : N ratio of 300 or more, priming effects would likely drive a net increase in total ecosystem C storage, although tree mortality or depletion of soil N over time could eventually limit this increase.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, Cleveland and Liptzin (2007) suggested that an average soil microbial N:P ratio might be a more appropriate index of ecosystem nutrient limitation than plant N:P ratios. A recent study showed that the biogeochemical consequences of N deposition in temperate forests may be driven by the stoichiometry of the dominant trees and their associated microbes (Midgley and Phillips, 2016) while van Diepen et al (2017) found that fungi exposed to chronic nitrogen enrichment are less able to decay leaf litter. All of these studies point to the importance of multi-resource interactions in nutrient cycling in soils.…”
Section: Discussionmentioning
confidence: 99%
“…Plant control over organolytic activities is relatively stronger under EcM trees in temperate forest soils (Brzostek & Finzi, ). In particular, activities of proteases, chitinases, polyphenol oxidases and acid phosphatases are relatively greater in EcM‐dominated habitats (Phillips & Fahey, ; Brzostek & Finzi, ; Phillips et al ., ; Yin, Wheeler & Phillips, ; Midgley & Phillips, ), whereas cellulase activity is greater in AM‐dominated habitats (Cheeke et al ., ) in temperate forests. Brzostek et al .…”
Section: Plant Nutritionmentioning
confidence: 99%